Unpredictability of maternal sensory signals: entropy as a novel metric of caregiving behavior - Holmberg, Eeva (fi=Turun yliopisto|en=University of Turku|, 2023)
Emerging evidence suggests that exposure to unpredictable maternal sensory signals in caregiving behavior (characterized as entropy rate) during infancy affects child neurocognitive development. However, the research paradigm is new, and little is known regarding which parental characteristics are related to unpredictable sensory signals or how signal unpredictability is related to more traditional caregiving measurements. Moreover, the longitudinal effects of signal unpredictability on child development are understudied. The aims of our study were 1) to examine how maternal mental health and selfregulation are associated with unpredictability of maternal sensory signals in caregiving behavior (Study I); 2) to investigate how unpredictable maternal sensory signals associate with maternal sensitivity (Study II) and 3) to explore whether unpredictable sensory signals relate to child self-regulation at 5 years of age (Study III). The study sample comprised mother-child dyads from the FinnBrain Birth Cohort Study. The main findings showed that higher maternal anxiety symptoms during the pre- and postnatal period together with low self-regulation capacity were associated with greater signal unpredictability during infancy. During the period of infancy to toddlerhood, unpredictable sensory signals and sensitivity were modestly correlated with each other. Exposure to unpredictable sensory signals, especially at very high levels, was associated with children’s poorer self-regulation at 5 years of age. The findings suggest that the combination of high maternal anxiety symptoms and low self-regulation capacity seems to constitute a specific risk for higher unpredictability of maternal sensory signals in caregiving behavior. Results identify unpredictable sensory signals as a characteristic of parental care that is independent of quality measures, namely maternal sensitivity. Unpredictability of maternal sensory signals is a potentially important aspect of early caregiving behavior associated with the development of child self-regulation capacity. KEYWORDS: caregiving behavior, unpredictable sensory signals, sensitivity, anxiety symptoms, depressive symptoms, self-regulation

Kasvava tutkimusnäyttö osoittaa, että altistuminen ennustamattomille aistiärsykkeille äidin hoivakäyttäytymisessä (entropia) vauvaiän aikana on yhteydessä lapsen neurokognitiiviseen kehitykseen. Tutkimussuuntaus on kuitenkin uusi ja toistaiseksi tiedetään vähän, mitkä vanhemman ominaisuudet ovat yhteydessä ennustamattomiin aistiärsykkeisiin tai miten signaalien ennustamattomuus on yhteydessä perinteisempiin hoivakäyttäytymistä arvioiviin mittareihin. Lisäksi aistiärsykkeiden ennustamattomuuden pitkäaikaisia vaikutuksia lapsen kehitykseen on tutkittu vielä vähän. Tutkimuksen tavoitteena oli 1) tutkia miten äidin raskausaikaiset ja synnytyksen jälkeiset ahdistus- masennusoireet ja itsesäätelykyky ovat yhteydessä ennustamattomiin aistiärsykkeisiin äidin hoivakäyttäytymisessä (Tutkimus I), 2) tutkia miten ennustamattomat aistiärsykkeet ovat yhteydessä äidin sensitiivisyyteen (Tutkimus II), ja 3) selvittää ovatko äidin ennustamattomat aistiärsykkeet yhteydessä lapsen itsesäätelyyn 5 vuoden iässä (Tutkimus III). Tutkimusotokset koostuivat FinnBrainsyntymäkohorttitutkimukseen osallistuvista äiti-lapsipareista. Keskeisten tulosten mukaan äidin korkeat ahdistusoireet raskausaikana ja synnytyksen jälkeen yhdessä heikon itsesäätelykyvyn kanssa olivat yhteydessä korkeampaan aistiärsykkeiden ennustamattomuuteen. Vauva- ja taaperoiässä aistiärsykkeiden ennustamattomuus ja sensitiivisyys olivat kohtalaisesti yhteydessä toisiinsa. Altistuminen ennustamattomille aistiärsykkeille, erityisesti hyvin korkealle tasolle, oli yhteydessä lapsen heikompaan itsesäätelyyn 5-vuoden iässä. Tulokset osoittavat, että korkeat ahdistusoireet yhdessä heikon itsesäätelykyvyn kanssa näyttävät olevan erityinen riskitekijä korkeammalle aistiärsykkeiden ennustamattomuudelle. Aistiärsykkeiden ennustamattomuus näyttää olevan erillinen osa-alue hoivan laatua arvioivista mittareista kuten äidin sensitiivisyydestä. Äidin ennustamattomat aistiärsykkeet ovat mahdollisesti tärkeä osa-alue hoivakäyttäytymisessä, joka on yhteydessä lapsen itsesäätelyn kehitykseen. ASIASANAT: hoivakäyttäytyminen, ennustamattomat aistiärsykkeet, sensitiivisyys, ahdistusoireet, masennusoireet, itsesäätely